Development of Augmented Reality-Assisted Learning Materials on the Coordination System to Enhance Systems Thinking Skills - Yesica Renita Putri; Dewi Lengkana; Noor Fadiawati; Viyanti Viyanti (Postgraduate, University of Mataram, 2026)
This study aimed to develop Augmented Reality-assisted instructional materials on the coordination system, to describe their practicality in improving students’ systems thinking skills, and to evaluate the effectiveness of the developed instructional materials. The research employed a Research and Development (R&D) approach based on the 4-D development model, which consists of four stages: define, design, develop, and disseminate. The instruments used included a needs analysis questionnaire, validity questionnaire, practicality questionnaire, learning implementation observation sheet, and a systems thinking skills pretest-posttest. The results showed that the instructional materials were highly valid, with content validity of 89.5%, construct validity of 94.8%, and attractiveness validity of 97.2%. The Augmented Reality-assisted instructional materials were practical for improving systems thinking skills, as indicated by the implementation of learning activities, which reached 92.5%. Product evaluation responses revealed that most students provided highly positive assessments, with a percentage of 97.22%, while teachers’ assessments reached 95.7%. Furthermore, the instructional materials were effective in enhancing systems thinking skills, as demonstrated by a high N-Gain score of 0.79 and a large effect size of 1.95. Based on these findings, the developed Augmented Reality-assisted instructional materials were effective in improving students’ systems thinking skills.